2011
DOI: 10.1186/1746-4811-7-30
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient rice green tissue protoplast system for transient gene expression and studying light/chloroplast-related processes

Abstract: BackgroundPlant protoplasts, a proven physiological and versatile cell system, are widely used in high-throughput analysis and functional characterization of genes. Green protoplasts have been successfully used in investigations of plant signal transduction pathways related to hormones, metabolites and environmental challenges. In rice, protoplasts are commonly prepared from suspension cultured cells or etiolated seedlings, but only a few studies have explored the use of protoplasts from rice green tissue.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
535
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 769 publications
(541 citation statements)
references
References 45 publications
4
535
0
2
Order By: Relevance
“…The total time needed for processing every 2.5 g of SDX to generate protoplasts is ;4 h (;1 h for preparing tissue strips and ;3 h for cell wall digestion). The efficiency of this system is comparable to or better than many others (Manders et al, 1992;He et al, 2007;Riazunnisa et al, 2007;Yoo et al, 2007;Sonntag et al, 2008;Tang et al, 2010;Zhang et al, 2011;Guo et al, 2012;Huddy et al, 2012;Pitzschke and Persak, 2012); however, the throughput (;4 h for every 2.5 g SDX) was still low. We then found that a debarked stem segment (Figure 1; see Supplemental Figure 1 online) with intact SDX can be used directly to release SDX protoplasts by submerging the stem into the enzyme digestion solution.…”
Section: Resultsmentioning
confidence: 99%
“…The total time needed for processing every 2.5 g of SDX to generate protoplasts is ;4 h (;1 h for preparing tissue strips and ;3 h for cell wall digestion). The efficiency of this system is comparable to or better than many others (Manders et al, 1992;He et al, 2007;Riazunnisa et al, 2007;Yoo et al, 2007;Sonntag et al, 2008;Tang et al, 2010;Zhang et al, 2011;Guo et al, 2012;Huddy et al, 2012;Pitzschke and Persak, 2012); however, the throughput (;4 h for every 2.5 g SDX) was still low. We then found that a debarked stem segment (Figure 1; see Supplemental Figure 1 online) with intact SDX can be used directly to release SDX protoplasts by submerging the stem into the enzyme digestion solution.…”
Section: Resultsmentioning
confidence: 99%
“…12143) following the manufacturer's manual. The rice protoplasts were isolated and transformed according to the published methods described previously (Bart et al, 2006;Zhang et al, 2011). For vacuole releasing, intact rice protoplasts were treated by vacuole lysis buffer (10 mM EDTA, 10 mM EGTA, and 95 mM mannitol or sorbitol, pH 8.0 adjusted by 1 M Tris) for 3 to 5 min, and ready for microscopy observation.…”
Section: Subcellular Localization Assaymentioning
confidence: 99%
“…Sequences of oligonucleotides used for cloning of SERF1 and MAPK5 are listed in Supplemental Table 6 online. Subsequently, plasmids were transformed into rice shoot protoplasts according to Zhang et al (2011). After transformation and incubation, the protoplasts were lysed and the renilla luciferase (RLUC) signal was measured with the Dual-Luciferase reporter assay kit using a GloMax 20/ 20 luminometer (Promega).…”
Section: Split-luciferase Assaymentioning
confidence: 99%
“…Rice shoot protoplasts were obtained and transformed with the 35S: SERF1-CFP construct according to Zhang et al (2011). Fluorescence imaging of the protoplasts was performed using a confocal laser scanning microscope (SP5; Leica Microsystems).…”
Section: Subcellular Localization Of Serf1mentioning
confidence: 99%
See 1 more Smart Citation